2015
DOI: 10.4038/tar.v26i1.8070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the level of dietary rice bran with or without phytase, on performance and egg parameters of laying Japanese quail

Abstract: Cost of quail feed formulations can be reduced substantially by using cheap cereal by-products such as rice bran (RB) at higher levels. The objective of this study was to determine the maximum inclusion levels of dietary RB with or without exogenous phytase, for laying Japanese quail. In a completely randomized design with a 3 x 2 factorial arrangement, 108 quails in 36 cages received six experimental diets ad libitum from 8 to 15 week. Experimental factors were three dietary RB inclusion levels (20, 30 and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Currently, there is little data on the influence of ERB supplementation on laying a Provided per kilogram of diet: all-trans-retinyl acetate, 2.0 mg; cholecalciferol, 0.025 mg; all-rac-α-tocopherol acetate,1.75 mg; menadione (menadione sodium bisulfite), 1.9 mg; riboflavin, 7 mg; thiamine (thiamine mononitrate), 2.1 mg; pyridoxine, 3.2 mg; niacin, 55 mg; Ca pantothenate, 15 mg; cobalamin, 0.04 mg; folic acid, 0.85 mg; D-biotin, 0.1 mg. hens; thus, there are no comparisons could be made with other studies. However, it has been reported that the effect of dietary supplementation of 20%, 30%, and 40% rice bran had no significant difference on yolk, albumin, shell (Abeyrathna et al 2015), which were in line with our finding. In addition, other studies showed that increasing of RB level up to 10% (Nobakht 2007) or 15% (Ersin Samli et al 2006) had no effect on egg-quality Note: CON (control), basal diet; T1, CON + 0.01% extracted rice bran; T2, CON + 0.02% extracted rice bran; SEM, standard error of the mean.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, there is little data on the influence of ERB supplementation on laying a Provided per kilogram of diet: all-trans-retinyl acetate, 2.0 mg; cholecalciferol, 0.025 mg; all-rac-α-tocopherol acetate,1.75 mg; menadione (menadione sodium bisulfite), 1.9 mg; riboflavin, 7 mg; thiamine (thiamine mononitrate), 2.1 mg; pyridoxine, 3.2 mg; niacin, 55 mg; Ca pantothenate, 15 mg; cobalamin, 0.04 mg; folic acid, 0.85 mg; D-biotin, 0.1 mg. hens; thus, there are no comparisons could be made with other studies. However, it has been reported that the effect of dietary supplementation of 20%, 30%, and 40% rice bran had no significant difference on yolk, albumin, shell (Abeyrathna et al 2015), which were in line with our finding. In addition, other studies showed that increasing of RB level up to 10% (Nobakht 2007) or 15% (Ersin Samli et al 2006) had no effect on egg-quality Note: CON (control), basal diet; T1, CON + 0.01% extracted rice bran; T2, CON + 0.02% extracted rice bran; SEM, standard error of the mean.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were in agreement with the results presented by Dung et al (2012) reported that levels of 2.5 and 3% of rice bran oil had beneficial effect on lowering egg yolk cholesterol. But the results of Safamehr and Attarhoseini (2011) and Abeyrathna et al (2014) showed that inclusion of the rice bran in laying hens diets did not significantly influence cholesterol in egg yolk as compared with the control group.…”
Section: Resultsmentioning
confidence: 93%
“…These results were in agreement with those of Amoah and Martin (2010) who reported that performance of laying type quail fed 20% full fat rice bran was comparable with those fed control diet. On the other hand, Abeyrathna et al (2014) reported that the total egg production of quail fed diet containing 40% rice bran was significantly lower than that of birds fed 20 and 30% of rice bran.…”
Section: Resultsmentioning
confidence: 97%
“…Santos et al (2013) found feed consumption did not differ significantly with phytase supplementation by the lower mineral diets during 21 days experimental period. Abeyrathna et al (2014) stated that phytase supplementation did not affect feed consumption and FCR of Laying Japanese Quail. All these results agreed our results during 35 days experimental period in this experiment.…”
Section: Feed Consumption and Feed Conversion Efficiencymentioning
confidence: 99%